Cardiac arrest from acute myocardial infarction complicated with sodium-glucose cotransporter 2 inhibitor-associated ketoacidosis. Issue 2 (February 2017) - Dai, Zhehao; Nishihata, Yosuke; Kawamatsu, Naoto; Komatsu, Ikki; Mizuno, Atsushi; Shimizu, Masato; Toya, Nozomi; Ishimatsu, Shinichi; Komiyama, Nobuyuki
Abstract: Euglycemic diabetic ketoacidosis (DKA) has been recognized as a potentially fatal complication related to sodium-glucose cotransporter 2 (SGLT2) inhibitors. Herein, we report a patient of out-of-hospital cardiac arrest, with an initial cardiac rhythm of ventricular fibrillation, who was subsequently diagnosed with acute myocardial infarction, complicated with SGLT2 inhibitor-associated euglycemic DKA. The patient survived and achieved nearly full functional recovery. This report calls for increased attention to SGLT2 inhibitors' fatal complications, as well as their proper use. <Learning objective: Euglycemic diabetic ketoacidosis could develop in patients using sodium-glucose cotransporter 2 inhibitors. It is a potentially lethal complication and needs more attention. Physicians who prescribe this class of drugs should be aware of this complication. Meanwhile, research to elucidate patient characteristics that are more susceptible to this complication is urgently awaited.>